Techno-economic Feasibility of Energy Supply of Water Pumping in Palestine by Photovoltaic-systems, Diesel Generators and Electric Grid - Ibrik, Imad H. (International Journal of Energy Economics and Policy, 2020)
The agriculture sector nowadays in Palestine relies mostly on conventional energy sources and traditional irrigation ways. Considering some factors such as high costs of fossil fuels and providing new electrical network, especially to remote areas and where grid electricity is either inaccessible or expensive to expand, therefore a solar PV powered irrigation system can be a practical choice for irrigating. In this paper, a PV-Powered DC water pump system design for irrigation is presented, techno-economic feasibility of using solar Photovoltaic (PV) systems for water pumping to replace a diesel engines and electric pumps also is presented. The PVSyst simulation software was used for convenience and monetary issues. Solar PV water pumping is found to be more economically in comparison to diesel or electricity water pumping in rural, urban and remote regions in Palestine. The investment payback for some PV water pumping systems instead of diesel is found to be around one year and around 7 years for replacement of electrical conventional pumps. Keywords: Solar water pumping; Solar Photovoltaic; Techno-economic analysis; Remote areas. JEL Classification: Q42 DOI: https://doi.org/10.32479/ijeep.8816